Full-stack JavaScript strategies the hidden parts every mid-level developer needs to know - McGregor, Milecia (O'Reilly Media, Inc., 2024)
As a working software developer, you know how to complete your tasks with solid code, whether it's on the frontend or backend. Now you're ready to move to the next level in your career, and you need to understand the subtle yet deep skills it takes to become a senior developer. This practical book shows you everything it takes to create a full-stack web application hosted on a cloud platform. Senior staff engineer Milecia McGregor helps you see how the whole system works and how senior developers arrive at technical decisions. You'll learn about design and development principles and when to apply them. You'll also discover strategies for working with different teams and understand how the product team makes its decisions.